Newnes data communications pocket book - Tooley, Michael H.; Winder, Steve (Oxford ; Boston : Newnes, 2002)
Despite the complexity of the subject, this wealth of information is presented succinctly and in such a way, using tables, diagrams and brief explanatory text, as to allow the user to locate information quickly and easily. Thus the book should be invaluable to those involved with the installation, commissioning and maintenance of data communications equipment, as well as the end user. *A practical engineer's reference that puts the key information at your fingertips *Covers essential data, techniques and working practice *This update covers the latest international regulations.
Preface; LAN software; Networking; Operating systems; Bluetooth and wireless LANs; Fault-finding on RS-232 systems; Optical fibre technology and the IEEE interface standard; Multiplexing (TDM and FDM); Data compression; Digital line systems; On-line services; Digital radio systems; Glossary of data communications terms; Index.
Includes index.
Keywords: Data transmission systems -- Handbooks, manuals, etc; Electronic books